2016
DOI: 10.1212/wnl.0000000000002930
|View full text |Cite
|
Sign up to set email alerts
|

Consensus for NF clinical trials

Abstract: The neurofibromatoses (NFs) can result in substantial morbidity in affected patients. In order to accelerate the development of effective therapies for NF-related tumor and nontumor manifestations, the development of standardized meaningful outcome measures for clinical trials is critical. The Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) International Collaboration was established with the goal to develop consensus recommendations for outcome measures and endpoints in future NF trials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Three previous supplements published in Neurology ® in 2013, and 2016, and 2021 set forth a variety of recommendations for clinical trial design, gathered stakeholder perspectives on clinical trials, and generated empirical evidence on the reliability of proposed outcomes. 4 6 A summary of all currently recommended measures is available at the REiNS website at https://ccrod.cancer.gov/confluence/display/REINS/Recommendations ; these include the use of volumetric magnetic resonance imaging (MRI) analysis to assess response in clinical trials and the use of various functional and patient-reported outcome measures to evaluate clinical benefit. Many of these measures were incorporated into the SPRINT registration trial, which established the efficacy of selumetinib for treatment of inoperable plexiform neurofibromas in pediatric patients with NF1.…”
mentioning
confidence: 99%
“…Three previous supplements published in Neurology ® in 2013, and 2016, and 2021 set forth a variety of recommendations for clinical trial design, gathered stakeholder perspectives on clinical trials, and generated empirical evidence on the reliability of proposed outcomes. 4 6 A summary of all currently recommended measures is available at the REiNS website at https://ccrod.cancer.gov/confluence/display/REINS/Recommendations ; these include the use of volumetric magnetic resonance imaging (MRI) analysis to assess response in clinical trials and the use of various functional and patient-reported outcome measures to evaluate clinical benefit. Many of these measures were incorporated into the SPRINT registration trial, which established the efficacy of selumetinib for treatment of inoperable plexiform neurofibromas in pediatric patients with NF1.…”
mentioning
confidence: 99%
“…[4][5][6] The Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) International Collaboration has played a key role in the creation and dissemination of outcome measures for clinical trials of neurofibromatosis type 1 (NF1), neurofibromatosis type 2 (NF2), and schwannomatosis. [7][8][9] Recognizing the potential benefits of patient engagement on this work, REiNS invited patients with neurofibromatosis (NF) and caregivers to join the organization in 2017. In 2019, we administered an online survey of REiNS members to evaluate this patient representative program.…”
mentioning
confidence: 99%
“…Since its founding in 2011, the Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) International Collaboration has worked to develop standardized, practical, and clinically meaningful outcome measures for clinical trials in these conditions. Two previous supplements published in Neurology ® in 2013 1 and 2016 2 set forth a variety of recommendations that are summarized in the table.…”
mentioning
confidence: 99%